New method to reduce NOx emissions of diesel engines: electronically controlled steam injection system - Parlak, A.; Ayhan, V.; Ust, Y.; Sahin, B.; Cesur, I.; Boru, B.; Kokkulunk, G. (MANEY PUBLISHING, 2012)
In this study, the electronically controlled water steam injection (ESI) system was introduced as a new method to reduce NOx emissions. In this system, the energy required for obtaining steam was supplied from exhaust gases. Throttling by injector, pressured and heated water, which is in the form of saturated liquid, becomes superheated steam; thus, the corrosion problem caused by condensation is prevented. It was determined in full load condition engine tests that NOx emissions reduce up to 33%, power and moment increase up to 3% and specific fuel consumption decrease up to 5%. When a steam injection system was tried in engine running with 20% biodiesel, it was determined that all the emission parameters, also including NOx, reduced. As a result, the ESI system is considered to be an important method that can be adapted easily in cruise ships, ferries sailing in continental waters and merchant ships in order to reduce NOx emissions.
Keywords: Diesel engine; Steam; Performance; Biodiesel; Emissions; NOx; TOBACCO SEED; EMULSIONS; OIL; YIELD; FUEL; Energy & Fuels